Perfectionism and burnout among collegiate street dancers - Palos, Michaela C. 2000-
Among all the dance styles, cheer dance and street dance has been among the most athletic and competitive dances. Perfectionism and burnout are inevitable in these dances because of their athleticism and competitiveness. This study aimed to identify the correlation between perfectionism and burnout among N=81 collegiate street dancers from a collegiate street dance team located in Quezon City. Philippines. In addition, this study compared the subscales of perfectionism and symptoms of burnout within three teams of the same collegiate team members who competed in their inter-team brawl competition this December 2022. Sports Multidimensional Perfectionism Scale-2 evaluated the level of perfectionism by Gotwals and Dunn (2009), and the Athlete Burnout Questionnaire assessed the level of burnout by Raedeke and Smith (2001). The results of the study showed that there is a low correlation between perfectionism and burnout, implying a weak relationship between the subscales of perfectionism and symptoms of burnout in collegiate street dancers. However, pair doubt about action and reduced sense of athletic accomplishment, with a correlation of 0.56 has the highest correlation among all pairs. It implies that dancers who doubt their actions mostly feel they do not achieve their optimal performance, which leads to burnout. It was also found that one group. Team A, has the highest average on most of the subscales of perfectionism (Personal Standard. Perceived Parental Pressure. Perceived Coach Pressure, and Organization) and symptoms of burnout (Emotional and Physical Exhaustion and Sport Devaluation) compared with two other groups. Team A shows higher levels of perfectionism and burnout because its members have been competing for a long time in street dance.